Determination of antibiotic, ß-agonist, and non-steroidal anti-inflammatory drug residues in ground beef from USDA certified organic, natural, conventional, and market cow and bull sources - Bowling, Mitchell Brett, author; Belk, Keith, advisor (Colorado State University. Libraries, 2009)
In recent years, consumer demand for organic and "natural" products has increased, partly due to a perception that such products are healthier and contain fewer additives, including veterinary drugs and growth promotants. The study presented herein compared occurrence of veterinary drug residues in ground beef samples reflecting different livestock production classifications. We collected ground beef samples (N = 400) consisting of 90.0 ± 4.0% lean muscle tissue from a total of eight plants, two each reflecting production in the following categories: (1) USDA Certified Organic (n = 100); (2) USDA Process Verified Never Ever 3 (n =1 00); (3) conventionally raised fed beef (n = 100); and (4) ground beef derived from carcasses of market cows and bulls (n = 100). Liquid chromatography coupled with triple-quadrupole mass spectrometry (UPLC-MS) methods were developed for the following veterinary drugs: (1) Aminoglycosides (Gentamicin, Amikacin, and Neomycin); (2) ß-lactams (Penicillin, Ampicillin, and Desfuroylceftiofur); (3) Fluoroquinolones (Danofloxacin and Ciprofloxacin); (4) Macrolides (Erythromycin, Tylosin, and Tilmicosin); (5) Phenicols (Florfenicol); (6) Sulfonamides (Sulfamethazine and Sulfadimethoxine,); (7) Tetracyclines (Oxytetracycline, Chlortetracycline, and Tetracycline); (8) Streptogramins (Virginiamycin); (9) ß-agonists (Ractopamine and Zilpaterol); and (10) non-steroidal anti-inflammatory drugs (Flunixin and Phenylbutazone). Residues exceeding their respective US tolerance limit were found in six ground beef samples. Two USDA Certified Organic samples contained Ampicillin residues exceeding US tolerance limits. One USDA Process Verified Never Ever 3 sample contained a residue of Ractopamine exceeding US tolerance limits. One sample from the market cow and bull category contained a residue of Sulfadimethoxine that exceeded US tolerance limits, one contained a residue of Ampicillin that exceeded US tolerance limits, and one contained a residue of Phenylbutazone that exceeded US tolerance limits. Residues of Phenylbutazone exceeding US tolerance limits were also found in one sample from the conventional production category. Additionally, residues (below the US tolerance limit) of several classes of veterinary drugs were found in samples from the USDA Certified Organic and USDA Process Verified Never Ever 3 production categories, a finding that clearly demonstrates violation of zero-tolerance statutes set forth by the National Organic Program and USDA Process Verified Never Ever 3 marketing descriptors. In the USDA Certified Organic production category, residues were detected in eight Ampicillin, seven Penicillin, three Sulfamethazine, one Sulfadimethoxine, and one Ractopamine sample. In the USDA Process Verified Never Ever 3 production category, residues were detected in one Ampicillin, one Chlortetracycline, two Tetracycline, and six Ractopamine samples. These violations exceed the historical prevalence of veterinary drug residues reported by the National Residue Program and demonstrate the need for careful monitoring of animals administered veterinary drugs in order to prevent improper inclusion of unqualified animals in premium marketing programs, such as USDA Certified Organic and USDA Process Verified Never Ever 3 programs.
Keywords: antibiotics; drug residues; ground beef; organic products; animal sciences